RESEARCH DEVELOPMENT RELATED TO IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS IN INDONESIA - Ismul Aksan; Doddy Setiawan; Evi Gantyowati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
This study tries to investigate the development of accounting standard research from 7 accredited journal in Indonesia. We conduct a sample of 35 articles for the period 2003-2017. Each article will be classified based on research topics, research methods, and kinds of standards that was observed by the researchers. The most widely researched topics related to the Financial Accounting Standards are topics related to the IFRS-based Financial Accounting Standards. The most commonly used research method is analytical method as much as 21 articles (60%). Standards that was observed by 26 articles (74,3%) is the implementation of Indonesian IFRS-based Financial Accounting Standards (SAK-IFRS). The other observed Indonesian Governmental Accounting Standards (SAP), Indonesian sharia accounting standard (SAK Syariah) and Indonesian Accounting Standard Non Publicly Accountable Entities (SAK-ETAP) where each of them are 3 articles, 5 articles and 1 article. Keywords: Analisis, financial accounting standards, bibliography, IFRS, the Government Accounting Standards, SAK-ETAP, SAK Sharia.